ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN PENDUDUK LANJUT USIA DI KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Krisna, I Made Bagus; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
South Kuta District is the sub-district with the highest percentage increase in the number of elderly people in Badung Regency, which is equal to 0.14 percent. The aim of this research is to analyze the partial influence of health factors, level of religiosity, economic conditions, and family support on well-being; and analyze the role of family support in moderating the influence of the level of religiosity and economic conditions on welfare. The sample in this study was 140 elderly residents using purposive sampling and accidental sampling methods. The data analysis technique used was Moderated Regression Analysis (MRA) using Partial Least Squares (PLS). Based on the research results, it can be concluded that health factors, level of religiosity, and economic conditions partially have a positive and significant effect on welfare; family support has a positive but not significant effect on well-being; and family support strengthens the influence of the level of religiosity and economic conditions on the welfare of the elderly population in South Kuta District, Badung Regency. The government needs to pay attention to access to health services for the elderly, such as equitable health insurance for the elderly and socialization regarding health insurance that needs to be more intensive.